2020
DOI: 10.3201/eid2608.191806
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline and Sitafloxacin Combination Therapy for Treating Highly Resistant Mycoplasma genitalium

Abstract: M ycoplasma genitalium is a sexually transmitted bacterium with marked capacity for developing antimicrobial resistance (1). Macrolides and 4th-generation fluroquinolones, such as moxifloxacin, have been the main agents displaying efficacy against M. genitalium. However, macrolide resistance has increased to >50% in many nations, and quinolone resistance is increasing (2-6). In Australia, 16% of M. genitalium strains are reported to have dual-class resistance (5), and Japan reports dual-class resistance of up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…In this strategy, patients were presumptively treated with DOX while awaiting detection of M. genitalium and MRM SNP typing using the ResistancePlus MG test (SpeeDx, Inc., Sydney, Australia). Patients infected with MRM-containing M. genitalium were treated with sitafloxacin (or moxifloxacin [MXF] in a subsequent study [ 67 ]), while those with the AZM-susceptible allele were treated with high dose azithromycin (2.5 g). This regimen increased microbiologic cure rates to 92.5%, even though prevalence of MRM was 62% in this patient population, and reduced the emergence of AZM resistance during treatment to 2.6% ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this strategy, patients were presumptively treated with DOX while awaiting detection of M. genitalium and MRM SNP typing using the ResistancePlus MG test (SpeeDx, Inc., Sydney, Australia). Patients infected with MRM-containing M. genitalium were treated with sitafloxacin (or moxifloxacin [MXF] in a subsequent study [ 67 ]), while those with the AZM-susceptible allele were treated with high dose azithromycin (2.5 g). This regimen increased microbiologic cure rates to 92.5%, even though prevalence of MRM was 62% in this patient population, and reduced the emergence of AZM resistance during treatment to 2.6% ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients infected with MRM-containing M. genitalium were treated with sitafloxacin (or moxifloxacin [MXF] in a subsequent study [ 67 ]), while those with the AZM-susceptible allele were treated with high dose azithromycin (2.5 g). This regimen increased microbiologic cure rates to 92.5%, even though prevalence of MRM was 62% in this patient population, and reduced the emergence of AZM resistance during treatment to 2.6% ( 66 , 67 ). Accordingly, the UK ( 42 ) and Australian ( http://www.sti.guidelines.org.au/sexually-transmissible-infections/mycoplasma-genitalium ) guidelines recommend resistance-guided treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Doxycycline combined with sitafloxacin also had a good therapeutic effect on multidrugresistant M. genitalium. At the same time, under this combined treatment there was only one parC G248T / S83I mutation and no gyrA mutations (56). Therefore, rotation and combination of medications provide a way to prevent drug resistance.…”
Section: Discussionmentioning
confidence: 89%
“…11 Durukan et al reported 11/12 cured MG infections using doxycycline and sitafloxacine combination therapy, after pristinamycin failure. 12 However, sitafloxacine is not available in France.…”
Section: Discussionmentioning
confidence: 99%